Let’s talk – face to face - Leow, Serena Wai Yee * (Star Media Group Berhad, 2023)
Many youngsters in Malaysia seem to be heavily leaning on the use of digital communication channels to connect with others, especially through social media and mobile instant messaging chatgroups.